2018
DOI: 10.1038/s41438-018-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling reveals regulatory mechanisms underlying corolla senescence in petunia

Abstract: The genetic regulatory mechanisms that govern natural corolla senescence in petunia are not well understood. To identify key genes and pathways that regulate the process, we performed a transcriptome analysis in petunia corolla at four developmental stages, including corolla fully opening without anther dehiscence (D0), corolla expansion, 2 days after anthesis (D2), corolla with initial signs of senescence (D4), and wilting corolla (D7). We identified large numbers of differentially expressed genes (DEGs), ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 55 publications
5
25
0
Order By: Relevance
“…The ABA-induced genes, PP2C , increased in their mRNA levels significantly from the phase of MA as we discovered, which could appear to dephosphorylate an essential component of the ABA pathway leading to the synthesis of hydrolytic enzymes and programmed cell death (PCD) [ 75 ]. This mediation proved coincident in petunia corolla senescence [ 49 ]. Whereas the three genes encoding PYL family proteins which act as abscisic acid sensors, were obviously down-regulated in LA compared with M, maybe demonstrating the transcriptional reduction of PYL homologs in extreme premature senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ABA-induced genes, PP2C , increased in their mRNA levels significantly from the phase of MA as we discovered, which could appear to dephosphorylate an essential component of the ABA pathway leading to the synthesis of hydrolytic enzymes and programmed cell death (PCD) [ 75 ]. This mediation proved coincident in petunia corolla senescence [ 49 ]. Whereas the three genes encoding PYL family proteins which act as abscisic acid sensors, were obviously down-regulated in LA compared with M, maybe demonstrating the transcriptional reduction of PYL homologs in extreme premature senescence.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of the RNA-seq technique for acquiring mRNA transcriptome profiling to investigate the probable function of genes, most Senescence-Associated Genes (SAGs) have been able to be characterized by such a technique. However, the transcriptome analyses of plant senescence has been operated only on a limited number of plants, including Arabidopsis [ 46 ], wheat [ 1 ], cotton [ 7 , 17 ], common tobacco [ 41 ], sorghum [ 47 ], maize [ 48 ], and petunia corolla [ 49 ], and more plants are required. Though the only transcriptome analysis of senescence in Nicotiana tabacum was reported by Li [ 41 ], it has laid focus on the metabolites of nutrient remobilization rather than the gene transcription regulating senescence.…”
Section: Introductionmentioning
confidence: 99%
“…RNAseq samples of Arabidopsis and rice were obtained from different tissues and developmental stages under drought and salt stress conditions (Table S7). The data were filtered using Trim_galore, a high-throughput sequence quality confine analysis tool (Brown et al, 2017;Wang et al, 2018). Then, the filtered reads were mapped to the Arabidopsis and rice reference genomes using HISAT2 (Yang-Ming et al, 2016).…”
Section: Rna-seq Data and Quantificationmentioning
confidence: 99%
“…However, the genetic regulatory mechanisms of flowering in A. amurensis under extremely low temperatures are unclear. Currently, both transcriptomics and proteomics have been widely used to identify genes in flowering in plants [21,22,23]. In the present study, we identified the key TFs involved in flowering in A. amurensis by combining transcriptomic and proteomic analyses.…”
Section: Introductionmentioning
confidence: 99%